Clinical Risk Factors of Post Operative Complications in Hypospadias Repair - Akmal Fawzi; Paksi Satyagraha; Besut Daryanto (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2022)
Objectives. Failed hypospadias refers to any hypospadias repair that leads to complications or causes patient dissatisfaction. Many factors influence the occurrence of complications, therefore this study aims to determine what risk factors can cause complications after hypospadias surgery.Methods. The study was conducted retrospectively by collecting 78 data of hypospadias patients who underwent surgery in Saiful Anwar General Hospital medical record from January 2015 until June 2019. age at the time of surgery, location of the external urethral meatus, degree of chordee, previous surgery history, type of urinary diversion, presence of Urinary Tract Infection (UTI), how many stages of surgery were performed, the surgical technique used at each stage and the complication recorded and analyzed.Results. Hypospadias patients who underwent surgery were 78 patients. The mean patient age was 9.96 years SD ± 6.959. Most of the ages were 11-18 years old with 28 patients. The location of the external urethral meatus was mostly found proximal to the penis of 40 patients. 44 patients were accompanied by mild chordee. 10 patients had previously undergone hypospadias surgery. 16 patients suffered from significant urinary tract infections but had no symptoms. 60 patients were inserted urethral catheter placement after hypospadias surgery. The most surgical technique used in stage 1 hypospadias surgery is Tubularized Incised Plate (TIP) Urethroplasty. While the technique used in 2 stage hypospadias surgery was Dorsal onlay preputial graft followed by TIP Urethroplasty. Complications that occurred in 1 stage hypospadias surgery were urethrocutan fistule in 9 patients and chordee in 1 patient. In 2 stage hypospadias surgery 3 patients obtained urethrocutan fistules, 2 patients with scrotal abscess and 1 patient obtained graft shrinkage. Age at surgery, location of Meatus Urethrae Externus (MUE), presence of UTI and also the choice of urinary diversion type correlated with the presence of complications. (P=0,004, P=0,033, P=0,049, P=0,000).Conclusions. Our results suggest that the success of hypospadias surgery is associated with age at surgery, location of MUE, presence of UTI and also the choice of postoperative urinary diversion type.